Nilai Nutrisi Dadih yang ditambahkan Khamir Asal Dadih - Yurliasni Yurliasni; Yusdar Zakaria; Yunasri Usman (Jurnal Agripet, 2014)
(Nutritive value of dadih added with yeast of dadih origin)ABSTRACT. Dadih is traditionally fermented buffalo milk product which is along with lactic acid bacteria (LAB), a diversity of yeast species involved in fermentation process. The existence of yeast in dadih gives positive contribution either in aroma or their role in securing a good product. There were three different dadih origin yeasts involved in this experiment (Candida curiosa, Brettanomyces custersii and Kluyveromyces lactis.) The objective of this research is to study more about growth and yeasts role on dadih fermentation in order to find positive value of yeast to keep nutritive value of dadih. Completely Randomized Designed used with four treatments. The treatments given was percentage of combined yeast culture which were P0 (buffalo milk + LAB), P1 (buffalo milk + LAB + 0,5% yeast culture), P2 (buffalo milk + LAB + 1,0% yeast culture), and P3 (buffalo milk + LAB + 1,5% yeast culture), by seven replication. The difference effect between treatment was tested by using Duncans Multiple Range Test. The Results showed that addition of yeast culture in dadih effect the pH, total of microorganism, degree of lactic acid, protein and dadih fat significantly. Overall dadih added with 1% yeast culture (P2) increase 14% degree of protein and decrease 2,7% degree of dadih fat.